Randomised trial of a brief physiotherapy intervention compared with usual physiotherapy for neck pain patients: outcomes and patients' preference. Issue 7482 (7th December 2004) - Moffett, Jennifer A Klaber; Jackson, David A; Richmond, Stewart; Hahn, Seokyung; Coulton, Simon; Farrin, Amanda; Manca, Andrea; Torgerson, David J
Abstract: Objectives Firstly, to compare the effectiveness of a brief physiotherapy intervention with "usual" physiotherapy for patients with neck pain. Secondly, to evaluate the effect of patients' preferences on outcome. Design Non-inferiority randomised controlled trial eliciting preferences independently of randomisation. Setting Physiotherapy departments in a community setting in Yorkshire and north Lincolnshire. Participants 268 patients (mean age 48 years) with subacute and chronic neck pain, who were referred by their general practitioner and randomly assigned to a brief physiotherapy intervention (one to three sessions) using cognitive behaviour principles to encourage self management and return to normal function or usual physiotherapy, at the discretion of the physiotherapist concerned. Main outcome measures The Northwick Park neck pain questionnaire (NPQ), a specific measure of functional disability resulting from neck pain. Also, the short form 36 (SF-36) questionnaire, a generic, health related, quality of life measure; and the Tampa scale for kinesophobia, a measure of fear and avoidance of movement. Results At 12 months, patients allocated to usual physiotherapy had a small but significant improvement in NPQ scores compared with patients in the brief intervention group (mean difference 1.99, 95% confidence interval 0.45 to 3.52; P = 0.01). Although the result shows a significant inferiority of the intervention, the confidence interval shows that the effect could be in the non-inferiority range for the brief intervention (below 1.2 points of NPQ score). Patients who preferred the brief intervention and received this treatment had similar outcomes to patients receiving usual physiotherapy. Conclusions Usual physiotherapy may be only marginally better than a brief physiotherapy intervention for neck pain. Patients with a preference for the brief intervention may do at least as well with this approach. Additional training for the physiotherapists in cognitive behaviour techniques might improve this approach further.